Legal Protection For Wife As A Victim Of Domestic Violence Based On Law No. 23 Of 2004 On The Elimination Of Domestic Violence - Saniah Saniah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses domestic violence, especially against wives, after the issuance of Law No. 23 of 2004 concerning